The Use of Various Media on Hatchability, Hatching Time and The Vitality of Honey Cricket Tillers (Gryllus mitratus) - Lumban Tobing, Ersan Riaji; Hanafi, Nevy Diana; Umar, Sayed (Indonesian Journal of Agricultural Research, 2020)
Crickets are the most demanded commodity because there have the most interest in ornamental livestock such as birds, while the presence of crickets in nature has diminwashed because their natural habitat has been increasingly eroded by city development. The important thing to consider in cricket farms was when incubating cricket eggs which requires special treatment to maintain their temperature and humidity. Thwas study aims toknow the hatching ability of cricket, egg hatching duration and the vitality of honey cricket age 0-10 days, in different media. The research was conducted at the Biology Laboratory of Animal Husbandry Study Program, Faculty of Agriculture, Universitas Sumatera Utara, Jl. A. Sofyan No. 3 Medan, which started from November 2018 until December 2018. The design used was a completely randomized design (CRD) 4 treatments (Q0: river sand hatch media; Q1: sand hatch media; Q2: kapok hatch media; Q3: rice straw hatch, and 5 replications (each conswasting of 100 honey cricket eggsÂ Grylus mitratus).The use of various media for honey cricket hatching eggs has a positive influence on the hatchability of eggs, the duration of hatching eggs and the vitality of honey crickets tillers.Â River sand hatching media (P0) is the best hatching media for the parameters of hatching eggs of honey cricket and the vitality of honey crickets tillers.